Benarkah Media Sosial Menjadi Pendorong Motivasi Mahasiswa Belajar Bahasa Asing Di Kota Bandung? - Mala Nurkamila; Tri Indri Hardini; Dadang Sunendar; Yulianeta Yulianeta (Jurnal Pendidikan Bahasa dan Sastra, 2022)
Motivation can encourage foreign language learners to always improve their abilities and knowledge. In addition, the media for learning is also needed to facilitate the process of exchanging information related to the knowledge that is being studied. This research was conducted to understand how motivation to the learning process of foreign language learners could be influenced by one of the learning media which is now developing so rapidly, namely social media. This study refers to a qualitative descriptive method by collecting data through a mixed questionnaire spread to students in universities in the area of Bandung. Based on the data obtained, it was found the fact that the respondents had the motivation of each underlying and encouraged them to learn foreign languages. In the learning process, the majority of respondents agreed that the latest social media can also encourage their motivation in learning a foreign language.